Two-Stage Urethroplasty with Buccal Mucosa for Penoscrotal Hypospadias Reconstruction in a Male with a 46,XX Karyotype - Pieter D'hulst; Jochen Darras; Steven Joniau; Pieter Mattelaer; Linsey Winne; Diederik Ponette (Urology Case Reports, 2017)
We present a case regarding a 32-year old African male with penoscrotal hypospadias, left cryptorchidism and a left inguinal hernia. There were moderate masculinization characteristics. He underwent a Lichtenstein hernia repair with perioperative biopsies of the left inguinal testis and epididymis. Microscopic examination showed a Sertoli-only left testis with Leydig-cell hyperplasia and the left epididymis consisted of ovarian tissue with corpora albicantia and maturing follicles. Endocrinological evaluation showed a sex-determining region Y (SRY) negative 46,XX karyotype. We successfully performed a two-stage urethroplasty with buccal mucosa graft to reconstruct his penoscrotal hypospadias.